RELATIVE IMPACT OF INSECTICIDAL APPLICATIONS ON POPULATION OF NATURAL ENEMIES IN OKRA - M. B. ZALA,; A. P. NIKOSHE,; T. M. BHARPODA, (The Bioscan, 2015)
An experiment was conducted at Anand Agricultural University, Anand to study the impact of insecticides on the activity of coccinellids and spiders, a potential predator of sucking pests during two consecutive seasons summer and kharif, 2012-13. Two insecticides i.e. thiamethoxam 25 WG (I1) and dimethoate 30 EC (I2) were evaluated on two different application strategies i.e. schedule based (S1) and need (ETLs) based (S2) with two different doses i.e. concentration (D1) and g a. i./ha (D2) for their adverse impact on natural enemies i.e. spiders and coccinellids. Among the insecticidal application strategies, the schedule based application of thiamethoxam 25 WG @ 0.0125% (S1I1D1) was relatively safer to the activity of these two predators in okra ecosystem by recording the highest population.